Surveying Antimicrobial Resistance: Approaches, Issues, and Challenges to Overcome - Jose Luis Capelo (Frontiers Research Topics, 2017)
Why Antibiotic Resistance? The use of antibiotics in human and veterinary medicine may have consequences beyond their intended applications. The "One Health" concept recognizes that the health of humans is connected to the health of animals and the environment. Progress in molecular genetics is facilitating the rapid evaluation of the essentiality of these targets on a genomic scale. In 2015, a group of researchers established the International Conference on Antibiotic Resistance (IC2AR).The primary objective of this meeting is to bring together scientists involved in antibiotic resistance prevention and control. The IC2AR conducted its inaugural world congress in January 2015 at Caparica (Portugal). Antimicrobial resistance presents a significant challenge to scientists in the field of infectious diseases. The full knowledge of how antibiotics resistance is evolving and being transmitted between hosts in different ecosystems is taking on great importance. Necessary action includes research to define the scope of the problem including its various sources. This eBook comprises a series of original research and review articles dealing with the epidemiology of resistance in animal and zoonotic pathogens, mobile elements containing resistance genes, the omics of antimicrobial resistance, emerging antimicrobial resistance mechanisms, control of resistant infections, establishing antimicrobial use and resistance surveillance systems, and alternatives strategies to overcome the problem of antimicrobial resistance worldwide. Gilberto Igrejas, José Luis Capelo and Patrícia Poeta Scientific Committee of IC2AR, February 20th, 2017Why Antibiotic Resistance? The use of antibiotics in human and veterinary medicine may have consequences beyond their intended applications. The "One Health" concept recognizes that the health of humans is connected to the health of animals and the environment. Progress in molecular genetics is facilitating the rapid evaluation of the essentiality of these targets on a genomic scale. In 2015, a group of researchers established the International Conference on Antibiotic Resistance (IC2AR).The primary objective of this meeting is to bring together scientists involved in antibiotic resistance prevention and control. The IC2AR conducted its inaugural world congress in January 2015 at Caparica (Portugal). Antimicrobial resistance presents a significant challenge to scientists in the field of infectious diseases. The full knowledge of how antibiotics resistance is evolving and being transmitted between hosts in different ecosystems is taking on great importance. Necessary action includes research to define the scope of the problem including its various sources. This eBook comprises a series of original research and review articles dealing with the epidemiology of resistance in animal and zoonotic pathogens, mobile elements containing resistance genes, the omics of antimicrobial resistance, emerging antimicrobial resistance mechanisms, control of resistant infections, establishing antimicrobial use and resistance surveillance systems, and alternatives strategies to overcome the problem of antimicrobial resistance worldwide. Gilberto Igrejas, José Luis Capelo and Patrícia Poeta Scientific Committee of IC2AR, February 20th, 2017